2016
DOI: 10.1080/08964289.2016.1189396
|View full text |Cite
|
Sign up to set email alerts
|

The Usability and Acceptability of an Adolescent mHealth HIV/STI and Drug Abuse Preventive Intervention in Primary Care

Abstract: Human Immunodeficiency Virus (HIV)/sexually transmitted infection (STI) risk behaviors among adolescents remain significant public health concerns. Shifts in policy and advances in technology provide opportunities for researchers and clinicians to deliver and evaluate mobile-health (mHealth) prevention programs in primary care, however, research is limited. This study assessed the usability and acceptability of Storytelling 4 Empowerment-a mHealth HIV/STI and drug abuse preventive intervention app-among adoles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 27 publications
(31 reference statements)
1
37
0
1
Order By: Relevance
“…Characteristics of eight recent, in-progress or completed technology-based interventions are shown in Table 2 [19, 20, 23, 3337]. Seven of the intervention studies are being conducted in the US [19, 20, 23, 3335, 37], and one in Canada [36].…”
Section: Technology-based Interventions For Drug-using Persons Livingmentioning
confidence: 99%
See 2 more Smart Citations
“…Characteristics of eight recent, in-progress or completed technology-based interventions are shown in Table 2 [19, 20, 23, 3337]. Seven of the intervention studies are being conducted in the US [19, 20, 23, 3335, 37], and one in Canada [36].…”
Section: Technology-based Interventions For Drug-using Persons Livingmentioning
confidence: 99%
“…Seven of the intervention studies are being conducted in the US [19, 20, 23, 3335, 37], and one in Canada [36]. Three of the studies reported trial outcomes [20, 23, 35], two of which are pilot trials with small sample sizes [20, 23], and one is a larger-scale efficacy trial [35].…”
Section: Technology-based Interventions For Drug-using Persons Livingmentioning
confidence: 99%
See 1 more Smart Citation
“…Data are from a larger study focused on the development and examination of a mobile-health HIV/STI and drug abuse preventive intervention (Córdova et al, 2015; Córdova et al, 2016). Data collection occurred between December 2013 and October 2014, and was approved by the University of Michigan’s Institutional Review Board.…”
Section: Methodsmentioning
confidence: 99%
“…Ecodevelopmental theory has been applied to develop a fuller understanding of how parent–adolescent communication shapes HIV/STI risk behaviors (Córdova, Huang, Pantin, & Prado, 2012). The theory may also have great utility for developing a fuller understanding of clinician–adolescent HIV/STI communication, yet research remains limited (Córdova et al, 2015; Córdova et al, 2016). Furthermore, social interaction theory affirms that clinician–adolescent communication does not happen in isolation, but rather occurs in a dynamic and reciprocal manner; therefore, incorporating aspects of interpersonal communication processes into an ecodevelopmental framework may be helpful.…”
Section: Ecodevelopmental and Interpersonal Communication Theorymentioning
confidence: 99%